Validitas Alat Ukur dalam Evaluasi Pendidikan: Kajian Konseptual tentang Jenis, Faktor Penentu, dan Implikasi Pengukuran - Ridha, Achmad Rasyid; Widyaningsih, Erna (TSAQOFAH, 2026)
Validity is a fundamental aspect of the measurement process because it determines the extent to which an instrument truly measures the construct it is intended to measure. This paper aims to discuss the concept of measurement validity comprehensively, including its definition, the distinction between validity and reliability, and various types of validity, namely content validity, construct validity, criterion-related validity, and face validity. Through a theoretical review and conceptual analysis of various literature sources, the paper also examines factors that affect validity, originating from the characteristics of the instrument, the respondents, the researcher, and environmental conditions. The discussion is further enriched with an explanation of commonly used validity testing methods, including correlation analysis, factor analysis, and expert judgment. This review emphasizes that validity is not only a technical aspect but also an ethical one in research, as it directly influences data quality, the accuracy of decision-making, and the integrity of research. In the digital era, challenges to instrument validity are becoming increasingly complex, thereby requiring continuous strategies for designing, evaluating, and refining the validity of measurement instruments across diverse research and educational evaluation contexts.